KEPEMIMPINAN KEPALA SEKOLAH BERBASIS GOTONG ROYONG LOBAAN (GOROL) DALAM MENDORONG PARTISIPASI ORANG TUA DI SDN KUTAKARANG 03 KABUPATEN PANDEGLANG - Syamsuri Abdurahman, Indra; Sholeh Hidayat; Enggar Utari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of school principal leadership based on the local wisdom of "Gotong Royong Lobaan" (Gorol) to enhance parental participation at SDN Kutakarang 03, Pandeglang Regency. The research is motivated by the low level of parental involvement, which was previously limited to formal and administrative support. Employing a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, display, and verification techniques. The results demonstrate that the principal successfully integrated Gorol values through social, communicative, and cultural approaches. This strategy effectively transformed parental participation from passive to active engagement, manifesting in physical participation (communal work), ideational participation (planning contributions), and emotional participation (learning support). The primary supporting factors include the strong culture of mutual cooperation within the community and open leadership, while inhibiting factors involve parents' time constraints and education levels. This study concludes that leadership based on local wisdom is an effective contextual strategy for strengthening school-community synergy in rural areas.